Representation of Empathy and Digital Politeness in Interpersonal Communication within Disaster-Related Volunteer Communities on Facebook - Hasibuan, Effiati Juliana; Lasahido, Nurrahmi (Universitas Syiah Kuala, 2025)
The increasing use of social media as a space for interpersonal communication in the volunteer community requires empathy and digital courtesy to maintain the effectiveness of group interaction and solidarity. This study aims to analyze how these characters are represented in communication between members of the Indonesian Disaster Care Forum (FPBI) on Facebook, focusing on patterns of empathetic expression, digital politeness practices, and interaction dynamics formed in online conversation spaces. This study used a qualitative approach with discourse analysis and netnography methods, involving observation of communication activities on community pages for three months, as well as in-depth interviews with 10 active informants. Data was collected through documentation of members' comments, uploads, and responses, then analyzed using thematic categorization techniques to identify emerging character values. The results showed that empathy was represented through supportive language, positive emotional responses, and verbal solidarity in emergency situations, while digital politeness was reflected in the use of respectful diction, ethical conflict negotiation patterns, and adherence to societal norms. In conclusion, this study confirms that the character of empathy and digital politeness plays a strategic role in strengthening the social cohesion and effectiveness of volunteer coordination in the digital space, and contributes theoretically to the study of social media-based interpersonal communication while offering practical implications for managing volunteer communities to remain adaptive, humanistic, and responsive in the digital ecosystem.